FINANCIAL INCLUSION IN THE USE OF DIGITAL BANKING SERVICES IN JAKARTA - Natsir, Khairina; Arifin, Agus Zainul; Ronald , Ronald (International Journal of Application on Economics and Business, 2023)
Financial inclusion involves providing access to safe, convenient and affordable financial services for other disadvantaged and vulnerable groups, including low-income, rural and undocumented communities, who have been underserved or excluded from the formal financial sector. One of the services is provided by the bank to support the smooth and easy banking activities such as in transactions and other activities. This study aims to investigate and find empirical evidence about Financial Inclusion in the Use of Digital Banking Services in Jakarta. The population of this study is people who have digital banking mobile banking services who are already working and domiciled in DKI Jakarta, while the object of research is limited to Financial Knowledge, Financial Literacy, and Financial Inclusion. The sampling technique used purposive random sampling. The primary data is getting from questionnaire distributed and filled out by respondents. Data analysis was carried out using SmartPLS software, where two categories of tests were carried out, namely the outer and the inner model tests. The results show that Financial Knowledge influenced on Financial Literacy, Financial Literacy significantly influenced on Financial Inclusion, Financial Knowledge significantly influenced on Financial Inclusion, and Financial Literacy significantly enable to mediate the influence of Financial Knowledge on Financial Inclusion.